A proposed vision for developing the academic performance of Saudi universities in light of lean management - Al-Rajhi, Elham Naief (Journal of Educational and Psychological Sciences, 2023)
The current research aims to develop a proposed vision for developing the university performance of Saudi universities under lean management, by highlighting the global models of lean management that have contributed to raising the efficiency of university performance and increasing their competitiveness. The descriptive analytical method was used. The results of the research resulted in the design of a proposed vision that seeks guidance... The opinions of decision makers indicate the importance of activating lean management in Saudi universities to reduce waste of all kinds, which will have a positive impact on the university’s ability. To face changes and developments efficiently and effectively. The research presented recommendations, the most prominent of which is that Saudi universities seek to adopt modern administrative methods that will maximize the added value of university operations by eliminating waste and continuous improvement. Therefore, it is necessary to choose qualified leaders who are convinced of the importance of continuous development and improvement, and who work to overcome the obstacles and difficulties facing the application of lean management in universities, with the aim of achieving a competitive advantage for Saudi universities and developing them. The performance of its employees, and achieving its desired vision and goals.
Keywords: lean management; university performance; university development; Saudi universities